Risk and outcomes of pulmonary fungal infection after pediatric lung transplantation. Issue 11 (18th September 2017) - Ammerman, Evan; Sweet, Stuart C.; Fenchel, Matthew; Storch, Gregory A.; Conrad, Carol; Hayes, Don; Faro, Albert; Goldfarb, Samuel; Melicoff, Ernestina; Schecter, Marc; Visner, Gary; Williams, Nikki M.; et al.
Abstract: Background: Prospective studies to determine associated risk factors and related outcomes for pulmonary fungal infection (PFI) after pediatric lung transplant (PLT) are lacking. Methods: NIH‐sponsored Clinical Trials in Organ Transplantation in Children enrolled PLT candidates, collecting data prospectively for 2 years post‐transplant. Demographics, signs/symptoms, radiology, pathology and microbiology were collected. Analyses evaluated for PFI‐related risks and outcomes. Results: In 59 PLT, pre‐transplant fungal colonization occurred in 6 donors and 15 recipients. Cystic fibrosis (CF) was associated with pre‐transplant colonization ( P < .01). Twenty‐five (42%) PLT had 26 post‐transplant colonizations (median = 67 days, range = 0‐750 days) with Candida (13), Aspergillus (4), mold (6) or yeast (3). Post‐PLT colonization was not associated with CF, age, or pre‐PLT colonization. Thirteen PFIs occurred in 10 (17%) patients, 3 proven ( Candida species) and 10 probable ( Candida [3], Aspergillus [3], Penicillium [3], and mold [1]). Pulmonary fungal infection was preceded by post‐PLT colonization with the same organism in 4 of 13 PFI, but post‐PLT colonization did not predict subsequent PFI ( P = .87). Older age at transplant was a risk for PFI ( P < .01). No mortality was attributed to PFI. Prophylaxis use was not associated with decreased post‐PLT colonization ( P = .60) or PFI ( P = .48). Conclusion: In PLT, PFI and fungal colonization are common but without associated mortality. Post‐PLT colonization did not predict PFI. Optimal prevention strategies require additional study.